Comparative Studies on Physical Properties of Urine and Urine-Oxalic Acid Mixture of Healthy Individual and Patients Suffering From Urinary Calculi - Shukla, P.C.; Chaube, K.K. (Asian Journal of Chemistry, 2010)
Field experiments were conducted during Kharif season, to study the influence of increasing rates of phosphorus and zinc containing chemical fertilizers on yield and uptake of these nutrients by soybean at Research Farm of Jawahar Lal Nehru Krishi Vishwavidyalaya Regional Agricultural Research Station and in the farmers' field, of Sagar, India. Results revealed that progressive doses of phosphorus and zinc elements significantly increased the grain and straw yield over control.